The 2005 BRAC Process: The Case to Save Maine’s Bases - Langhauser, Derek (Maine Policy Review, 2005)
Derek Langhauser gives a postmortem of Maine’s response to the Base Realignment and Closure (BRAC) Commission’s announcement of imminent closure of bases in Portsmouth-Kittery, Brunswick and Limestone. Although Maine did not “win back” the Brunswick facility, Maine rescued the facilities in Portsmouth-Kittery and Limestone, secured additional resources for the Bangor Air National Guard and Bangor Naval Reserve Center, and was granted an expansion of the Limestone accounting center. Maine’s response to the BRAC Commission’s original announcement is testament to the extraordinary capacity of the states’ people to work together in times of crisis
Keywords: Maine; military bases; Defense Base Realignment and Closure Commission; BRAC